Teachers’ Competency in Technology, Digital Innovation, and Creativity and Its Role in Supporting Curriculum Reform in Light of UNESCO’s Education 2030 Strategy - Ahmed, Rizwan (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
The aim of the study was to assess the effect of the teachers’ competencies in technology, digital innovation, and creativity on curriculum changes within the context of UNESCO’s Education 2030 Strategy. The change in global educational standards towards sustainable, digitally-driven, and inclusive frameworks makes the adaptability of educators an essential factor. The influence of these competencies on core curriculum reform was investigated using PLS-SEM. Responses were gathered from a structured questionnaire from 263 business education teachers from different universities in Karachi, Pakistan. This study also highlights the impact of incorporated institutional support along with a nurturing an innovative and creative mindset towards solving curriculum issues. It has been discovered that there is a definite impact concerning the teacher’s ability to facilitate curriculum transformation through digital and creative skills. The study provides new dimensions in respect of educational reforms and shifts within the policies of teaching and instructional systems intended for fulfilling the objectives of Education 2030. It stresses the need for purposeful eective investment in teacher training in creative digital pedagogy so that meaningful advancements towards curriculum changes can be accomplished